Applications and limitations of measuring environmental DNA as indicators of the presence of aquatic animals - Rees, Helen C.; Gough, Kevin C.; Middleditch, David J.; Patmore, James R.; Maddison, Ben C. (Wiley, 2015)
1. In Rees et al. (2014b), we reviewed the current status of environmental DNA (eDN A) tomonitor aquatic populations. Our aim was to focus on discus sion of methodologies used,application of eDNA analysis as a survey tool in ecology, and to include some innovativeideas for using eDNA in conservation and management. 2. Roussel et al. (2015) claim that analysis of Rees et al. (2014b) and other publicationshighlights the downsides of the method, and they suggest that some conclusions should betoned down. Many of their arguments were covered in our original paper (Rees et al. ,2014b); however, they make the point that modelling approaches should be encouraged, andwe fully agree with this suggestion. 3. Roussel et al. (2015) also claim that we neglected to recognize that there are two sourcesof imperfect detection (at the ﬁeld level and at the laboratory level). We feel that our reviewpaper implies this point. 4. Synthesis and applications. Roussel et al. (2015) reiterate many of the points made in theoriginal paper but do cover some additional areas that improve the debate on the use of envi-ronmental DNA (eDNA). Both the comment (Roussel et al., 2015) and our rebuttal clearlyhighlight that detailed laboratory protocols and rigorous ﬁeld sampling design are crucial fac-tors which require sufﬁcient reporting in the literature to allow for experimenta l comparisonand replication. Any development of a new method for eDNA detection should be compareddirectly with established ‘gold standard’ methods for the detection of the species or habitatunder investigation. None of the issues raised in Roussel et al. (2015) would alter our mainconclusions.